Interfacial dynamics - Kallay, Nikola 1942- (Surfactant science series, 2000)
An examination of the theoretical foundations of the kinetics and thermodynamics of solid-liquid interfaces, as well as state-of-the-art industrial applications, this book presents information on surface and colloidal chemical processes and evaluates vital analytical tools such as atomic force microscopy, surface force apparatus measurements, and photon correlation spectroscopy.